Thermal activation and temperature dependent PL and CL of Tb doped amorphous AlN and SiN thin films. Issue 8 (22nd July 2015) - Guerra, J. Andres; Montañez, Liz; Winnacker, Albrecht; De Zela, Francisco; Weingärtner, Roland; Seibt, M.
Abstract The effect of terbium (Tb) doping on the photoluminescence (PL) and cathodoluminescence (CL) spectra of amorphous aluminum nitride (a ‐AlN) and amorphous silicon nitride (a ‐SiN) thin films has been investigated for different temperature conditions. The samples were prepared by RF dual magnetron reactive sputtering technique with a Tb concentration of about ∼1 at% An enhancement of the light emission is obtained after thermal annealing treatments following the activation of luminescent centers. Furthermore, the Tb related integrated light emission intensity is reported exhibiting a continuous increase with the samples temperature well below thermal quenching for both materials. This behavior suggests a phonon assisted energy migration mechanism which contributes to the effective energy transfer from the matrix to the Tb ions. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)